2010
DOI: 10.1007/s10499-010-9373-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary niacin on growth and body composition of two Indian major carps rohu, Labeo rohita, and mrigal, Cirrhinus mrigala (Hamilton), fingerlings based on dose–response study

Abstract: An 15 week two set of feeding experiments were conducted to determine the dietary niacin requirement of Indian major carp fingerlings Labeo rohita and Cirrhinus mrigala, using casein gelatin-based diet. In both experiments, six isonitrogenous (40%) and isoenergetic (15.35 kJ g -1 ) test diet, with graded levels of niacin (0-50 mg kg -1 dry diet) in gradation of 10 mg kg -1 dry diet, were formulated. In first experiment, fingerling of L. rohita (4.20 ± 1.22 cm; 0.632 ± 0.67 gm) were randomly stocked, in triplic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 20 publications
6
16
0
Order By: Relevance
“…This requirement is less than the requirement reported for brook trout 95, gilthead seabream 63–83, Pacific salmon 150–200 (Halver, ; NRC, ) but higher than the requirement reported for channel catfish 14 (Halver, ), rainbow trout 10–50 (Poston & Wolfe, ), channel catfish 7.4 (Ng, Serrini, Zhang, & Wilson, ), African catfish 33 mg/kg (Morris, Backer, & Davies, ), Indian catfish 25 (Mohamed & Ibrahim, ) and comparable to the requirement of common carp 28‐50 (Halver, ), L . rohita, 33, C. mrigala 30 (Ahmed, ), grass carp 34.01‐42.08 (Li et al., ) mg/kg of diet. The discrepancy in the niacin requirements possibly because of the variations in fish size, quality of the diet, laboratory conditions, species differences, methodology and assessment criteria (Mohamed & Ibrahim, , NRC, , Jiang et al., ; Xia et al., ; Li et al., , ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This requirement is less than the requirement reported for brook trout 95, gilthead seabream 63–83, Pacific salmon 150–200 (Halver, ; NRC, ) but higher than the requirement reported for channel catfish 14 (Halver, ), rainbow trout 10–50 (Poston & Wolfe, ), channel catfish 7.4 (Ng, Serrini, Zhang, & Wilson, ), African catfish 33 mg/kg (Morris, Backer, & Davies, ), Indian catfish 25 (Mohamed & Ibrahim, ) and comparable to the requirement of common carp 28‐50 (Halver, ), L . rohita, 33, C. mrigala 30 (Ahmed, ), grass carp 34.01‐42.08 (Li et al., ) mg/kg of diet. The discrepancy in the niacin requirements possibly because of the variations in fish size, quality of the diet, laboratory conditions, species differences, methodology and assessment criteria (Mohamed & Ibrahim, , NRC, , Jiang et al., ; Xia et al., ; Li et al., , ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been accomplished on niacin requirement of fish species including brook trout Salvelinus fontinalis , rainbow trout Salmo gairdneri , common carp Cyprinus carpio , channel catfish Ictalurus punctatus, Japanese amberjack Seriola quinqueradiata , hybrid tilapia Oreochromis niloticus x O. aureus , gilthead seabream Sparus aurata , African catfish Clarias gariepinus , stinging catfish Heteropneustes fossilis , Pacific salmon Oncorhynchus kisutch (Halver, ; NRC, ), rohu Labeo rohita , mrigal Cirrhinus mrigala (Ahmed, ), Tilapia, Oreochromis niloticus (Jiang et al., ), grass carp Ctenopharyngodon idella (Wu et al., ; Li et al., ) and blunt snout bream Megalobrama amblycephala (Li et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Niacin is known as one of the most important water‐soluble vitamins for the maintenance of normal metabolic and physiological function in fish (Ahmed ). Study showed that niacin deficiency induced high mortality, anaemia, fin and skin haemorrhages in channel catfish ( Ictalurus punctatus ) (Ng et al .…”
Section: Introductionmentioning
confidence: 99%
“…Protein content of R. rita ranged between 17.2-19.55%. Protein content of medium size (19.55%) group was comparatively higher than other size groups and Indian major carps (IMCs), Labeo rohita (12.84%) (Ahmed, 2011) and similar to Cirrhinus mrigala (19.10%) and Catla catla (19.60%) (Gopakumar, 1997). Average protein content of R. rita (18.12%) was higher than that of many other catfishes like Mystus vittatus (15.62%), Clarias batrachus (14.78%), Wallago attu (17.00%) and is similar to bagridae catfish Sperata aor (19.05%) (Kamal et al, 2007;Memon et al, 2010) and Sperata seenghala (20.06%) (Mohanty et al, 2012).…”
Section: Proximate Compositionmentioning
confidence: 99%